The impact of bring-your-own-device on work practices in the financial sector - Mphahlele, Palesa (Department of Information Systems, 2016)
Bring-your-own-device (BYOD) refers to the practice of allowing the employees of an organisation to use their own computers, smartphones, or other devices for work purposes. This has brought a tremendous change in today's working environment. Organisations are faced with many technology trends which have the potential to create a competitive advantage in terms of both performance and efficiency. This paper follows a qualitative approach in which 15 interviews were conducted and a survey covering of 87 respondents was distributed. The findings show that the financial sector interpret s BYOD as a strategy that can create a competitive advantage to provide benefits of increased productivity, flexibility in the workforce, more autonomy, and contribute to the cost - efficiency of the business. There was also a disregard of policy formulation for BYOD from management which created a problem as employees became despondent that their personal devices were n o t allowed to access the corporate network. In addition, the findings revealed that work practices have to be re - defined and policies have to be drawn up in order to protect the company's assets and to provide guidelines. To guide the research in this emerging area, a review of several established theories that have not yet been applied to BYOD were used to form part of the proposed framework, which aims to provide a mechanism in the workplace to evaluate the impact of BYOD. This paper used exploratory analysis where six major influences of work practices were identified: 1) Change in behaviour; 2) Impact on workload; 3) Changes in motivation of individuals; 4) Re-definition of work practices; 5) Impact on overall performance; and 6) Approach required for industry. It was possible to associate them to several related constructs in IS literature which exposed possibilities for future theory-building efforts. The main influences on work practices are discussed with respect to the proposed framework.